Comparative Potential of Antibacterial Activity of Marine Plants for the Development of Natural Antimicrobial Agents: A Review - Zikria, Nazila Nazwa; Nurhadis, Nurhadis (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Antibiotic resistance remains a major global health concern, driven by the misuse and overuse of antibiotics, which has resulted in multidrug-resistant bacteria such as methicillin-resistant Staphylococcus aureus (MRSA) and extended-spectrum beta-lactamase-producing Escherichia coli (ESBL-E. coli), leading to increased morbidity, mortality, prolonged hospital stays, and rising healthcare costs. To address this challenge, the search for alternative antibacterial agents that are natural, sustainable, and environmentally friendly has become urgent. Marine plants, including red macroalgae (Rhodophyta), brown algae (Phaeophyta), green algae (Chlorophyta), and seagrasses, produce secondary metabolites such as flavonoids, alkaloids, terpenoids, tannins, and sulfated polysaccharides with promising antibacterial properties. This systematic review analyzed 320 articles from PubMed, Google Scholar, and ScienceDirect, of which eight met the inclusion criteria, to compare the antibacterial potential of marine plant extracts against Gram-positive and Gram-negative pathogenic bacteria. The findings indicated that species such as Kappaphycus alvarezii, Corallina officinalis, Eucheuma spinosum, Sargassum polycystum, Caulerpa racemosa, and Padina australis exhibited antibacterial activity ranging from weak to very strong depending on species, extraction methods, solvents, concentrations, and environmental conditions, with K. alvarezii showing the highest inhibition zone of up to 26 mm against Bacillus subtilis and Vibrio species. The antibacterial mechanism is believed to involve membrane disruption, alteration of permeability, and inhibition of protein and DNA synthesis. In conclusion, marine plants demonstrate strong potential as sources of natural antibacterial agents that may reduce dependence on conventional antibiotics and mitigate the global antibiotic resistance crisis, though further research is required to standardize extraction methods, isolate active compounds, and validate efficacy and safety through MIC, MBC, and in vivo studies before clinical and industrial application.